Levels and dimensions of urban renewal in the region of luz from the experience of spoliation to the struggle of socio-spatial classes: from the experience of spoliation to the struggle of socio-spatial classes - Petrella, Guilherme Moreira (Risco - Journal of Architecture and Urbanism, 2021)
The Region of Luz, downtown São Paulo, has been the target of several urban renewal plans since the 1970s, which aim to reverse the process of socio-spatial degradation. Among these plans, those proposed in the 21st century converge due to their forms of action: spatial restructuring in the real estate overlap and infrastructure carried out through public-private partnerships, which centralize productive capital (real), unproductive capital (fictitious) and the State (laws, financing, public policies and monopoly on the use of violence). They guide to the immediate constitution of the global financial real estate complex. However, despite the architectural and urban strategies that conceive formal differentiations relative to social differentiations, their "truth" is economic viability. In this sense, the “right to housing” appears and is realized as a “right to property”.